Potential of Trichoderma harzianum and Bacillus cereus as biocontrol of Ganoderma boninense in oil palm - Ahmed Abufana, Ghazala Saad (2016)
Sustainability of oil palm industry is crucial for sustaining Malaysia’s gross domestic product (GDP) by agricultural sector. However, without positioning efforts in eliminating or controlling Ganoderma disease encountered by this commodity crop, sustainability is not attainable. Thus, primary emphasis on developing early control or preventative measures that will contribute to a sustainable environment as well as cater this catastrophic is crucial. Therefore, this study was designed with the objectives: i)To investigate Trichoderma harzianum and Bacillus cereus antagonistic bio-inoculant potential in inhibiting Ganoderma boninense growth and ii)To determine the effects on vegetative growth and suppression of G. boninense infection in oil palm seedlings pre-inoculated with T. harzianum and B. cereus consortium. In order to achieve the objectives set for the present study, cultures of UPM29 (T. harzianum) and UPM15 (B. cereus) were isolated from rhizosphere of oil palm from plantation in a preliminary study. In this current study, all microbial isolates were subjected to morphological and molecular identification and screened for its antagonistic activity against G. boninense in vitro. The antagonistic activities were evaluated via dual culture test, culture filtrate assay, mycelial growth test, chitinase and β-glucanase assay. All the experiments above were repeated three times using completely randomized design (CRD) with eight replications. Nonetheless, nursery trial was conducted at Ladang 15, Faculty of Agriculture, UPM for a duration of 24 weeks on four months old oil palm seedlings (D×P) that were artificially inoculated with pathogenic (UPM13) G. boninense based on a newly developed artificial inoculation method known as dip, place and drench (DPD). Eight treatments with six individual replicates were designed for this nursery trial and conducted as randomized completely block design (RCBD). In addition, preparation of biological control agent (BCA) inoculants, the spore suspension were adjusted to a concentration of 6.0 × 107 conidia mL-1 for fungal isolate and 1×1012 CFU for bacterium. Disease assessments were analyzed based on disease severity (DS) of foliar, roots and disease reduction (DR). As a result, UPM15 and UPM29 demonstrated significant antagonistic activities against G. boninense growth by exhibiting a PIRG value of 72.9% and 95.7% via culture filtrate test and hyphae malformation and ii shrinkage in mycelial growth test respectively and exhibited ability in producing lignocellulolytic enzymes; chitinase and β-glucanase. In the nursery trial conducted, single application of B. cereus was found to be the most effective treatment in suppressing Ganoderma disease of oil palm with DR rate of 94.8% followed by single application of T. harzianum (79.0%). In addition, single application of both BCAs pointed out that B. cereus (13.3 g) was the BCA accountable in contributing an increase in the root dry weight and T. harzianum for the top dry weight (14.1 g). However, seedlings treated with the mixture of BCAs gave the highest dry root weight of 17.4 g compared to all other treatments. Hence, based on the results of this present study, UPM15 strain (B. cereus) may be an excellent option of BCA to be applied in the commercial oil palm nurseries prior to field transfer and tested in the fields where high incidence of Ganoderma disease were recorded for disease suppression.